Incidence and severity of anaphylaxis and hypersensitivity in trials of intravenous pertuzumab plus trastuzumab or the fixed-dose combination of pertuzumab and trastuzumab for subcutaneous injection for HER2-positive breast cancer. (January 2023) - Swain, Sandra M.; Tan, Antoinette R.; Gianni, Luca; Kuemmel, Sherko; Dang, Chau T.; Schneeweiss, Andreas; O'Shaughnessy, Joyce; Liu, Haiying; Aguila, Christian; Heeson, Sarah; Macharia, Harrison; Yang, Ke; et al.
Abstract: Aim: To characterise risk of anaphylaxis/hypersensitivity with intravenous pertuzumab plus trastuzumab (PH IV), the fixed-dose combination of pertuzumab and trastuzumab for subcutaneous injection (PH FDC SC) or concomitant chemotherapy to support potential administration of PH FDC SC by healthcare professionals outside clinics. Methods: A cumulative search for anaphylaxis/hypersensitivity (Roche Standard Adverse Event Group Terms) was performed for all pivotal trials cited in the current EMA P IV/PH FDC SC summaries of product characteristics: MBC: NCT00567190, NCT02402712; EBC: NCT01358877, NCT00545688, NCT00976989, NCT02132949, NCT03493854 and NCT03674112. Occurrence, incidence and severity of events were analysed and a time–trend analysis (by cycle) was performed. Results: This analysis includes 4772 patients who received PH IV and/or PH FDC SC. Incidence of all-grade (grade ≥3) anaphylaxis/hypersensitivity events: 3–11% (≤2%) for PH IV MBC trials; 1–13% (0–3%) for PH IV EBC trials; and 2–3% (<1%; not related to PH FDC SC) for PH FDC SC EBC trials. Discontinuations due to anaphylaxis/hypersensitivity were rare for PH IV (generally <1% except two arms of TRYPHAENA: 1% and 3%); no discontinuations of PH FDC SC have been recorded so far. Time–trend analysis showed that most events were reported during the first 6–8 cycles with concurrent chemotherapy, with a decrease in later cycles (except MetaPHER). Conclusion: PH IV and PH FDC SC were well tolerated, with few grade ≥3 anaphylaxis/hypersensitivity events reported with PH IV and no grade ≥3 related events with PH FDC SC. Most events occurred during chemotherapy. Highlights: PH can be administered intravenously or subcutaneously. These are used to treat HER2-positive breast cancer, often combined with chemotherapy. P, H or chemotherapy can cause anaphylaxis/hypersensitivity. Analysis of breast cancer trials showed low incidence of anaphylaxis/hypersensitivity. Discontinuations due to anaphylaxis/hypersensitivity were rare for PH.